A cross sectional study on respiratory related morbidities at cotton factories in Hyderabad, Telangana - Mummadi, Mahesh Kumar; Kusneniwar, Govind N. (International Journal Of Community Medicine And Public Health, 2017)
Background: In the last few years, globalization and rapid industrial growth lead to the emergence of occupational health issues. Byssinosis is a form of reactive airway disease, caused by exposure to cotton dust in inadequately ventilated working conditions. Cotton dust and fibres has been associated with deteriorating the respiratory function. Studies report that byssinosis is to an extent of 40% among textile workers. There were very few studies in Telangana. Hence, this study was conducted with an objective to identify the magnitude of respiratory related morbidities among workers in cotton factories. Methods: A cross sectional study was conducted during October to December 2013 in the randomly chosen two cotton factories in the outskirts of Hyderabad. All the employees of the cotton factories were included in the study. Information about socio demographic characteristics, general health condition was collected. A highly validated Medical Research Council (MRC) UK Respiratory questionnaire was used to collect data on respiratory morbidities. Data was entered in MS Excel and analysed using Epi info 7. Results: A total of 159 employees were participated in the study. Males were 9.4%, females were 90.6%. Mean age was 34.25 (±10). It was noted that 3.8% had history of asthma, 2% pneumonia, 13.2% hypertension and 3.8% had diabetes. As per MRC dyspnoea scale, in the last one month, grade 2 dyspnoea was seen in 32 % and grade 3 seen in 17%. Around 64 % has been working for more than 5 years and 36 % has been working for less than 5 years in the cotton factory. It was found that the duration of exposure is statistically significant with grade 2 dyspnoea in participants working in cotton factories. Conclusions: In the present study it can be inferred that the employees in cotton factories are prone to occupational hazards. Inhalation of cotton dust resulting in respiratory morbidities. Increased morbidities are seen in employees with more duration of exposure.